FACILITATING NURSING RESEARCH: A PROFESSIONAL MANDATE FOR PERIOPERATIVE NURSES - Michael, Rene (Operating Room Nurses Association of Canada Journal, 2007)
Health care and health care technology are becoming increasingly complex and expanding at an unprecedented pace. To thrive within this milieu, nursing as a profession must not only keep up with the pace but also set the pace for the future of health care. Nurses are constantly challenged to expand their ‘comfort zone’ by presenting creative approaches to health care, and developing new and innovative interventions that make a difference to the health status of patients and the community as a whole. As a consequence of this challenge, the question is raised: How do we as perioperative nurses expect to be competent technically, demonstrate independent judgement and skilled decision- making, and keep our knowledge base and practice current? The answer is through research.